2017
DOI: 10.3390/ma10101189
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Tribological Performance of Carbonitride Coatings Doped with W, Ti, Zr, or Cr Deposited on AISI 316L Stainless Steel

Abstract: Carbonitride (CNx) coatings have existed for several decades but are not well understood. Related studies have indicated that CNx coatings exhibit behaviors comparable to diamond-like carbon (DLC) coatings. Metal-doped CNx coatings are expected to show superior performance to single CNx coatings. In this study, a CNx coating and a group of CNx coatings with 6 at. % metal doping (W, Ti, Zr, or Cr) were prepared on biograde AISI 316L stainless steel (SS316L) substrates, and they were then characterized and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Oxidative wear, adhesive wear, and abrasive wear are the main material removal mechanisms for stainless steels and other alloys [ 11 , 17 , 18 , 19 , 20 , 21 ]. Those tribological performances were intensively dependent on the normal loads, counterparts, temperature, and lubricant conditions [ 16 , 17 , 22 , 23 , 24 ]. Vereschaka reported that the friction coefficient and adhesion effect change substantially with different high temperature conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative wear, adhesive wear, and abrasive wear are the main material removal mechanisms for stainless steels and other alloys [ 11 , 17 , 18 , 19 , 20 , 21 ]. Those tribological performances were intensively dependent on the normal loads, counterparts, temperature, and lubricant conditions [ 16 , 17 , 22 , 23 , 24 ]. Vereschaka reported that the friction coefficient and adhesion effect change substantially with different high temperature conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 79 carbonitride coatings doped with 6 at% W, Ti, Zr, or Cr were prepared on biograde AISI SS316L substrates. The antimicrobial test used Staphylococcus aureus.…”
Section: Biomedical and Bioelectronic Applicationsmentioning
confidence: 99%
“…66,67,68 Various investigations on Zr-carbonitride coatings have been undertaken to study synthesis parameters, 69 characterization, 70 and optical 71 and biomedical applications. [72][73][74][75][76][77][78][79] It is comparatively difficult to deposit Zr-based coatings compared to Ti-or Cr-based coatings using evaporationrelated physical vapor deposition (PVD) methods since Zr has high melting point, low vapor pressure, and high contamination susceptibility by oxygen and carbon. As a result, fewer studies exist in the literature about Zr-based coatings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of dental and orthodontic implants, some studies show that biofilms caused by attachment of bacteria are responsible for about 65% of infections such as periodontal disease and peri-implant diseases [3]. To prevent these adverse effects, surface treatments are used, among which the deposition of coatings by PVD and CVD methods are one of the ways to improve their mechanical and biological properties [4][5][6][7][8]. In particular, the coatings should fulfill a number of functions, such as bacterial resistance, i.e., resistance to adhesion and colonization of bacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Coatings with the highest C concentration (22 at.%) have been shown to increase the antibacterial ability against Staphylococcus aureus, but also meet the requirement for HGF (human gingival fibroblasts) biocompatibility. Tests of CN x -doped W, Ti and Zr coatings for antibacterial activity and wear are presented in [6]. It was shown that the CN x -Zr coating, whose surface had the highest hydrophilicity, provided the best antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%